2012
DOI: 10.1093/innovait/ins133
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Cancer

Abstract: Childhood cancers are uncommon, accounting for only 0.5% of all cancers in the UK. Approximately, 1500 children are diagnosed with cancer in the UK every year. Despite it being a rare occurrence, cancer still remains the largest cause of death in the 1–14 year age group, amongst whom it counts for 20% of all deaths. Although most adult cancers affect the lung, breast, bowel and prostate, the majority of childhood cancers are haematological and central nervous system (CNS) tumours. The primary care physician's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Although, it is the second most common of death for the general population, cancer is ranked at the first disease which is cause of death of children from late infancy through early adulthood (Bleyer, 1990). Research showed that 20 per cent of all death between 1 and 14 years old children is related to the childhood cancers (Smith & Phillips, 2012).…”
Section: Cancer In Childhoodmentioning
confidence: 99%
“…Although, it is the second most common of death for the general population, cancer is ranked at the first disease which is cause of death of children from late infancy through early adulthood (Bleyer, 1990). Research showed that 20 per cent of all death between 1 and 14 years old children is related to the childhood cancers (Smith & Phillips, 2012).…”
Section: Cancer In Childhoodmentioning
confidence: 99%